Comparison of Natural Honey and Metformin on Pancreatic Histopathology in STZ- Induced Diabetic Rats - Ozra Nasrolahi; Fereshte Khaneshi; Fatemeh Rahmani (Fasa University of Medical Sciences, 2014)
Background; Objective: The use of natural antioxidants is a new approach in controlling diabetes. In this study, the effect of natural honey (a powerful antioxidant) was compared with metformin (a prevalent drug used for diabetes) on histological changes of pancreas in diabetic rats.Materials; Methods: 30 male rats, weighting 180-220 gram were randomly divided into six groups including C: non diabetic rats receiving distilled water (0.5 ml), CH: non diabetic rats receiving honey (1g/kg b.w), CD: diabetic rats administered with distilled water (0.5 ml), D.H: honey treated diabetic rats (1g/kg b.w), DM: Metformin administrated-diabetic rats (100 mg/kg), and DMH: Metformin + honey-co-treated diabetic animals.Diabetes was induced by a single dose of Streptozotcin (65 mg/kg i.p). The animals were treated by oral gavage daily for a month. After treatment, the pancreatic tissues of the animals were excised, prepared, and stained with H & E method.Results: The results showed that the diameter and the number of islands of the pancreas in diabetic control rats have more significant decrease (p<0.001) than non-diabetic control rats. Diameter of the islands in DMH group had significant increase compared with DH and DM groups (p<0.05). Moreover, atrophy and destruction of the islet cells and the nucleus were observed in DC group. We faced improvement of these complications in treatment groups.Conclusion: Natural honey can have healing effect on the pancreas tissue of diabetic rats. Due to the antioxidant properties of honey, combination of honey and metformin can have restorative effect on pancreatic tissue repair in diabetic rats.